Armonia, Franco & My Grandfather - Ladjointe, Xavier (France Spain, 2017)
Why and when did his grandparents come to France? His mother’s silence leads the narrator to take her to Spain, back to her Spanish family.
Verzio Film Festival Submission
Keywords: Documentary films